دور تدريب الموارد البشرية في تحسين جودة الخدمة الفندقية - حسيني سعد; محمد مصطفى بن طالب; عبد الكريم مسعودي (جامعة الوادي University of Eloued, 2025)
" هدفت هذه الدراسة إلى معرفة دور تدريب الموارد البشرية في تحسين جودة الخدمة الفندقية من خلال أبعادها المتمثلة في: (الاعتمادية، الاستجابة، التعاطف، الضمان، الجوانب الملموسة) في فندق سوف –الوادي، والتحقق من مدى وجود اختلاف في جودة الخدمة الفندقية تبعا لاختلاف للبيانات الشخصية والوظيفية لعينة البحث. ولتحقيق أهداف الدراسة تموضع مجموعة من الأسئلة والفرضيات، وتم جمع البيانات الميدانية من خلال الاعتماد على أداة الاستبيان، وقد تم توزيع استمارات الاستبيان على عينة عشوائية بلغت 35 عاملا لدى فندق سوف –الوادي، وتم استرجاع 30استمارة استبيان صالحة للتحليل، وبعد تحليل البيانات واختبار الفرضيات باستخدام الحزمة الإحصائية SPSS.V.21 ، توصلت الدراسة إلى النتائج التالية: وجود أثر إيجابي ذو دلالة إحصائية لتدريب الموارد في البشرية في تحسين جودة الخدمة الفندقية بفندق سوف –الوادي، عند مستوى دلالة (α≥0.05)؛ وجود أثر إيجابي ذو دلالة إحصائية لتدريب الموارد في البشرية في تحسين جميع أبعاد جودة الخدمة الفندقية (الاعتمادية، الاستجابة، التعاطف، الضمان، الجوانب الملموسة) بفندق سوف –الوادي، عند مستوى دلالة (α≥0.05)؛ لا توجد فروق ذات دلالة إحصائية عند مستوى المعنوية (0.05) لمستوى التدريب في فندق سوف –الوادي- يعزى لمتغير الجنس؛ لا توجد فروق ذات دلالة إحصائية عند مستوى المعنوية (0.05) لمستوى التدريب في فندق سوف –الوادي- يعزى لمتغير العمر؛ توجد فروق ذات دلالة إحصائية عند مستوى المعنوية (0.05) لمستوى التدريب في فندق سوف –الوادي- يعزى لمتغير الدورات التدريبية؛ توجد فروق ذات دلالة إحصائية عند مستوى المعنوية (0.05) لمستوى التدريب في فندق سوف –الوادي- يعزى لمتغير الأقدمية في العمل؛ "This study aimed to know the role of human resources training in improving the quality of hotel service through its dimensions represented in: (reliability, responsiveness, empathy, guarantee, tangible aspects) in Souf Hotel - Al-oued, and to verify the extent to which there is a difference in the quality of hotel service according to the difference in the personal and functional data of the research sample. To achieve the objectives of the study, a set of questions and hypotheses were placed, and field data were collected by relying on the questionnaire tool, and the questionnaire forms were distributed to a random sample of 35 workers at the Souf Hotel - Al-oued, and 30 questionnaire forms valid for analysis were retrieved, and after analyzing the data and testing the hypotheses using the statistical package SPSS.V.21, the study reached the following results: - The existence of a statistically significant positive impact of human resource training in improving the quality of hotel service at Souf Hotel - Al-oued, at the level of significance (α 0.05)؛ - The existence of a statistically significant positive impact of human resource training in improving all dimensions of hotel service quality (reliability, responsiveness, empathy, assurance, tangible aspects) at Souf Hotel – Al-oued, at the level of significance (α 0.05)؛ - There were no statistically significant differences at the level of morale (0.05) for the level of training in the Souf Hotel - the valley - attributed to the gender variable; - There were no statistically significant differences at the level of moral (0.05) for the level of training in the Souf Hotel - the valley - attributed to the age variable; - There are statistically significant differences at the level of morale (0.05) for the level of training in the Souf Hotel - Al-oued - due to the variable of training courses; - There are statistically significant differences at the level of morale (0.05) for the level of training in the Souf Hotel - Al-oued - attributed to the variable of seniority at work;
ماستر
Keywords: موارد بشرية، تدريب الموارد البشرية، خدمة فندقية، جودة الخدمة الفندقية، فندق سوف –الوادي.; Human resourcrs; Human resources training; Hotel service; Hotel service quality; Souf- Al-oued Hotel.